VaR and expected shortfall: a non-normal regime switching framework - Elliott, Robert J., author; Miao, Hong, author; Quantitative Finance, publisher (Colorado State University. Libraries, 2009)
We have developed a regime switching framework to compute the Value at Risk and Expected Shortfall measures. Although Value at Risk as a risk measure has been criticized by some researchers for lack of subadditivity, it is still a central tool in banking regulations and internal risk management in the finance industry. In contrast, Expected Shortfall (ES) is coherent and convex, so it is a better measure of risk than Value at Risk. Expected Shortfall is widely used in the insurance industry and has the potential to replace Value at Risk as a standard risk measure in the near future. We have proposed regime switching models to measure value at risk and expected shortfall for a single financial asset as well as financial portfolios. Our models capture the volatility clustering phenomenon and variance-independent variation in the higher moments by assuming the returns follow Student-t distributions.
Published as: Quantitative Finance, vol.9, no. 6, pp.747-755, September 2009, https://doi.org/10.1080/14697680902849320.
Keywords: value at risk (VaR); expected shortfall (ES); regime switching; student-t distribution; fat tailed; volatility clustering